Harry Potter and the paradox of the 'expert'. Issue 3 (July 2016) - Griffiths, Dominic
Abstract : In this article, Dominic Griffiths reflects upon the current cultural gap between those who locate themselves as working 'on the inside' of the world of 'special educational needs' and the 'inclusion movement' and those who might be describe as 'mainstream classroom teachers'. Griffiths warns of the dangers of the dangers of 'enculturation' of the 'insiders' which can lead to communal visions of mainstream teachers as 'barriers to inclusion'. Equally, from 'outsider' perspectives, the world of special and inclusive education may be perceived as 'mysterious', hidden in a fog of arcane acronyms and populated by specialist 'experts'. The author calls for a conscious demystification of this world and an active reaching out to and nurturing of mainstream colleagues without whom, he argues, the inclusion project cannot succeed.